Porewater methane transport within the gas vesicles of diurnally migrating Chaoborus spp. - McGinnis, Daniel F.; Flury, Sabine; Tang, Kam W.; Grossart, Hans-Peter (Prof. Dr.) (Scientific Reports, 2017)
Diurnally-migrating Chaoborus spp. reach populations of up to 130,000 individuals m−2 in lakes up to 70 meters deep on all continents except Antarctica. Linked to eutrophication, migrating Chaoborus spp. dwell in the anoxic sediment during daytime and feed in the oxic surface layer at night. Our experiments show that by burrowing into the sediment, Chaoborus spp. utilize the high dissolved gas partial pressure of sediment methane to inflate their tracheal sacs. This mechanism provides a significant energetic advantage that allows the larvae to migrate via passive buoyancy rather than more energy-costly swimming. The Chaoborus spp. larvae, in addition to potentially releasing sediment methane bubbles twice a day by entering and leaving the sediment, also transport porewater methane within their gas vesicles into the water column, resulting in a flux of 0.01–2 mol m−2 yr−1 depending on population density and water depth. Chaoborus spp. emerging annually as flies also result in 0.1–6 mol m−2 yr−1 of carbon export from the system. Finding the tipping point in lake eutrophication enabling this methane-powered migration mechanism is crucial for ultimately reconstructing the geographical expansion of Chaoborus spp., and the corresponding shifts in the lake’s biogeochemistry, carbon cycling and food web structure.